(untitled) (Journal of Medicine, 2009)
Erythema nodosum is a common association of tuberculosis (TB), especially in this part of the world. Urogenital TB, although less common than other form of tuberculosis, may be associated with erythema nodosum along with other urinary complaints. Here we present a case of an old lady who presented with erythema nodosum with painless haematuria (microscopic) which was later found to be of tuberculous aetiology. Urine analysis yielded no acid-fast bacilli but culture on special media showed growth of Mycobacterium tuberculosis. Though erythema nodosum is usually associated with primary TB, our case revealed it can be found in cases where pulmonary focus is not the primary origin. The patient responded well to anti-tubercular drugs and is doing well on follow-up. Keywords: Erythema nodosum, Renal Tuberculosis, Urogenital Tuberculosis. doi: 10.3329/jom.v10i2.2831 J MEDICINE 2009; 10 : 132-134